Association of IGFBP-3 gene polymorphism g. 3.930 G>A with birth size and birth weight in crossbred beef cattle - Hartatik, T.; Priyadi, D. A.; Panjono, P.; Bintara, S.; Ismaya, I.; Budisatria, I. G. S.; Widyobroto, B. P.; Agus, A. (Diponegoro University, 2019)
Crossing between cattle breeds is the one way to improve the genetic quality of cattle. Controlling crosses using genetic markers will speed up the process. The IGFBP-3 gene is a potential marker of selection due to its role in regulating growth and metabolism in cattle. The aim of this study was to determine the effect of genotype on birth size and birth weight using IBFBP-3 gene marker. A total of 32 cattle consisted of 10 Brahman Cross cattle, 14 cattle results of Brahman Cross cow crosses with Belgian Blue bull, and 8 cattle results of Brahman Cross cow crosses with Wagyu bull. Sequences of 563 bp, including the part intron 2, exon 3, and the part intron 3. Genotyping was done by sequencing method and PCR-RFLP method with the restriction enzyme PvuII. An SNP was identified at location g 3,930 (G>A). Two genotypes were observed, namely GA and GG. The genotype did not affect the performance of birth (body weight, body length, height at withers, heart girth) of the research sample. Birth traits are influenced by the cattle breed, it can be seen that Brahman Cross cattle have a body length that is bigger than the other crossbred.